Distress and coping among youth during COVID-19: a national cross sectional study in France - Rezzoug, Dalila; Laurent, Isaura; Estevez, Mégane; Falissard, Bruno; Baubet, Thierry; Habran, Enguerrand; Oppenchaïm, Nicolas; Vandentorren, Stéphanie; De Stefano, Carla (Frontiers in Psychiatry, 2025)
BackgroundIn March 2020, the World Health Organization declared the SARS-CoV-2 outbreak a pandemic. In France, this led to school closures and strict lockdown measures. This unprecedented context disrupted the social lives and mental health of children and liadolescents.MethodsCONFEADO is a nationwide cross-sectional study designed to assess psychological distress in relation to coping strategies and emotional factors. Conducted between June 9 and September 14, 2020, the study included children aged 9 to 18 and their parents, including youth in child welfare services, all of whom provided informed consent. Data were collected via a self-administered, ad hoc web-based questionnaire distributed through national institutions, associations, and social media. For children in welfare services, a paper version was completed with the assistance of childcare professionals. The primary outcome was psychological distress, measured using the Children and Adolescents Psychological Distress Scale-10 (CAPDS-10). Additional variables included coping strategies (behavioral, cognitive, emotional, relational, spiritual), socio-environmental factors (e.g., living in housing with fewer than three rooms, low parental perceived social support), family conflict (e.g., increased conflict or violence), quality of family relationships (e.g., getting along with parents or siblings less than usual), eating habits (e.g., changes in appetite), and school-related stress (e.g., feeling overwhelmed by schoolwork).ResultsA total of 3,148 children and adolescents participated. In bivariate analyses, children who viewed religion as a positive or novel aspect of lockdown (spiritual coping) had a higher likelihood of experiencing moderate distress [OR = 1.26; 95% CI: 0.99–1.60; p = 0.06] and a significantly higher likelihood of experiencing severe distress [OR = 1.99; 95% CI: 1.44–2.74; p < 0.0001]. Relational coping was protective: lower perceived relational support was associated with increased risk of both moderate distress [OR = 0.79; 95% CI: 0.75–0.83; p < 0.0001] and severe distress [OR = 0.55; 95% CI: 0.49–0.61; p < 0.0001]. In multivariate models, severe distress was significantly associated with living in small housing, low parental perceived support, feeling overwhelmed by schoolwork, and appetite changes. Higher levels of behavioral and emotional coping difficulties and increased family conflict were also associated with greater distress.ConclusionsCoping strategies are key indicators of psychological distress in youth. Assessing how children and adolescents adapt during crises may provide deeper insights than symptom-based approaches alone. The role of spiritual coping in emotional adjustment warrants further clinical and research attention.